Analisis Kebutuhan Pengembangan E-LKM Berbasis Guided Inquiry Learning Terintegrasi Augmented Reality pada Materi Ikatan Kimia - Yulmi Mariani; Alizar (Lembaga Yasin AlSys, 2026)
Digital teaching materials have been widely developed for chemistry education, but studies specifically analyzing the need to develop electronic student worksheets (E-LKM) based on Guided Inquiry Learning (GIL) and integrated with Augmented Reality for chemical bonding remain limited. This study aims to analyze the need to develop GIL-based E-LKM integrated with Augmented Reality for Phase F chemical bonding at SMA Negeri 6 Padang. The study employed a quantitative approach with a survey design involving three chemistry teachers and 70 Phase F Grade XI students selected through purposive sampling. Data were collected through structured interviews and a needs analysis questionnaire and were subsequently analyzed using descriptive statistics in the form of percentages. The findings indicate that chemistry instruction remains dominated by lecture methods and the use of conventional teaching materials. A total of 60% of the students experienced difficulty understanding chemistry content, 65% stated that chemical bonding was difficult to understand, 68.6% considered the teaching materials used to be less engaging, 57.1% had never used E-LKM, and 82.9% had never used teaching materials that visualized concepts through images, text, or three-dimensional models. These findings indicate a need to develop GIL-based E-LKM integrated with Augmented Reality to facilitate more active and engaging learning and assist students in visualizing abstract concepts in chemical bonding. This study provides an empirical basis for developing digital teaching materials that address the needs of teachers and students in Phase F chemistry instruction.